Pharmacokinetic Characteristics, Tissue Bioaccumulation and Toxicity Profiles of Oral Arsenic Trioxide in Rats: Implications for the Treatment and Risk Assessment of Acute Promyelocytic Leukemia - Liu, Wensheng; Wang, Bin; Zhao, Yilei; Wu, Zhiqiang; Dong, Andi; Chen, Hongzhu; Lin, Liwang; Lu, Jing; Hai, Xin (Frontiers in Pharmacology, 2021)
Oral arsenic trioxide (ATO) demonstrated a favorable clinical efficiency in acute promyelocytic leukemia (APL) treatment. However, the pharmacokinetic characteristics, tissue bioaccumulation, and toxicity profiles of arsenic metabolites in vivo following oral administration of ATO remain to be characterized. The present study use the high performance liquid chromatography-hydride generation-atomic fluorescence spectrometry (HPLC-HG-AFS) to assess the pharmacokinetics of arsenic metabolites in rat plasma after oral and intravenous administration of 1 mg•kg-1 ATO. In addition, the bioaccumulation of arsenic metabolites in blood and selected tissues were evaluated after 28-day oral administration of ATO in rats at a dose of 0, 2, 8, 20 mg•kg-1•d-1. The HPLC-HG-AFS analysis were complemented with biochemical, hematological and histopathological evaluation conducted upon completion of ATO treatment. Pharmacokinetic results showed that arsenite (AsIII) reached a maximum plasma concentration rapidly after initial dosing, and the absolute bioavailability of AsIII was 81.03%. Toxicological results showed that the levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and white blood cells (WBC) in the 20 mg•kg-1•d-1 ATO group were significantly increased compared to the control group (p < 0.05). The distribution trend of total arsenic in the rat was as follows: whole blood > kidney > liver > heart. Dimethylated arsenic (DMA) was the predominant bioaccumulative metabolite in the whole blood, liver, and heart, while monomethylated arsenic (MMA) was the predominant one in the kidney. Collectively, these results revealed that oral ATO was rapidly absorbed, well-tolerated and showed organ-specific and dose-specific bioaccumulation of arsenic metabolites. The present study provides preliminary evidence for clinical application and long-term safety evaluation of oral ATO in the treatment of APL.